Early colonisation and temporal dynamics of the gut microbial ecosystem in Standardbred foals. (25th July 2018) - Quercia, S.; Freccero, F.; Castagnetti, C.; Soverini, M.; Turroni, S.; Biagi, E.; Rampelli, S.; Lanci, A.; Mariella, J.; Chinellato, E.; Brigidi, P.; Candela, M.
Summary: Background: Even if horses strictly depend on the gut microbiota for energy homeostasis, only a few molecular studies have focused on its characterisation and none on the perinatal gut microbial colonisation process. Objectives: To explore the perinatal colonisation process of the foal gut microbial ecosystem and the temporal dynamics of the ecosystem assembly during the first days of life. Study design: Longitudinal study. Methods: Thirteen Standardbred mare‐foal pairs were included in the study. For each pair, at delivery we collected the mare amniotic fluid, faeces and colostrum, and the foal meconium. Milk samples and faeces of both mare and foal were also taken longitudinally, until day 10 post‐partum. Samples were analysed by means of next‐generation sequencing of the 16S rRNA gene on Illumina MiSeq. Results: Our findings suggest that microbial components derived from the mare symbiont communities establishes in the foal gut since fetal life. After birth, an external transmission route of mare microorganisms takes place. This involves a rapid and dynamic process of assembling the mature foal gut microbiome, in which the founder microbial species are derived from both the milk and the gut microbial ecosystems of the mare. Main limitations: The inability to discriminate between live and dead cells, the possible presence of contaminating bacteria in low biomass samples (e.g. meconium and amniotic fluid), the limits of the phylogenetic assignment down to species level, and the presence of unassigned operational taxonomic units. Conclusions: Our data highlight the importance of mare microbiomes as a key factor for the establishment of the gut microbial ecosystem of the foal.